Hydronics 102 System Components - Boldt, Jeff; Keen, Julia (My University, 2015)
The article explores the common control devices in closed-loop hydronic systems (HS) namely expansion tanks (ET) and valves. Topics covered include the types of control needed in a hydronic system, the various kinds of ET including compression tanks and bladder tanks, the maximum design pressures for HS, the factors that must be considered when determining the size of a tank including system volume, and the differences between the types of valves including ball, butterfly and globe.
Boldt, J., & Keen, J. (2015). Hydronics 102 System Components. ASHRAE Journal, 57(9), 40-48.
Keywords: HYDRONICS; HYDRONIC heating systems; HEATING -- Equipment & supplies; TANKS; VALVES